Analisis Pengendalian Kualitas Produk pada Gudang PT. DSV Solutions Indonesia (Semarang Site) Menggunakan Metode FMEA - Rahmawati, Dwi Maudina; Anggraini, Denny Astrie (Fakultas Teknik UMRI, 2025)
PT. DSV Solutions Indonesia (Semarang Site) is a logistics company that provides storage and delivery services for PT. Semarang Autocomp Manufacturing Indonesia (SAMI). Between August and October 2024, several product defects were identified during the storage and delivery processes, including dented boxes, torn boxes, tangled wires, and peeled wires. These defects resulted in additional handling processes and had the potential to reduce customer trust. To analyze and address these issues, the Failure Mode and Effect Analysis (FMEA) method was applied to identify the root causes and effects of each defect, as well as to determine the priority for corrective actions. The analysis revealed that dented boxes had the highest Risk Priority Number (RPN) of 294, primarily caused by improper handling such as throwing packages. Meanwhile, tangled wires had an RPN of 252, attributed to poor material handling practices.